If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (2x + 3) + (2x + -1) = 180 Reorder the terms: 4x + (3 + 2x) + (2x + -1) = 180 Remove parenthesis around (3 + 2x) 4x + 3 + 2x + (2x + -1) = 180 Reorder the terms: 4x + 3 + 2x + (-1 + 2x) = 180 Remove parenthesis around (-1 + 2x) 4x + 3 + 2x + -1 + 2x = 180 Reorder the terms: 3 + -1 + 4x + 2x + 2x = 180 Combine like terms: 3 + -1 = 2 2 + 4x + 2x + 2x = 180 Combine like terms: 4x + 2x = 6x 2 + 6x + 2x = 180 Combine like terms: 6x + 2x = 8x 2 + 8x = 180 Solving 2 + 8x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8x = 180 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 180 + -2 8x = 180 + -2 Combine like terms: 180 + -2 = 178 8x = 178 Divide each side by '8'. x = 22.25 Simplifying x = 22.25
| (x-3)(5+2x)-(x-3)(x-6)= | | (5x-1)/3=3 | | 2x+30=2x-30 | | 9s(7s+7)+s(3s+6)= | | 4-5[2-(4y-3)]= | | (2x+4)+(4x-15)+93=180 | | b=80+(25+7)6 | | b=80+(25+7)3 | | 20.5=13+x | | Q=v/x | | =3x^2-10 | | 3x+(3x-48)+(2x-36)=180 | | 32-8w=8 | | (x+15)+(x+42)+89=180 | | =x^3-5x^2+x | | (x-29)+(x+32)+37=180 | | (9n+6m)+(7m+3)+(-2-4n)= | | 3+-10x=4+x | | 3b=11/2 | | =3x^2-10x | | 6(2-x/6=1 | | (2x-15)+(3x+10)+2x=180 | | 3(4-1)-7x=17 | | 6(7x+7)=-6(x+1) | | 4x-5[4(x+3)-(x-2)]-5= | | (r-2)(r+10)=-9 | | X-5/14=4/7 | | 1-(2)/(5)y=4x-3 | | (4x-28)+(9x-17)+30=180 | | (7+7d)+(-5+9m)= | | 2.2x=12.76 | | 6.3k-1.4+3.5=52.5 |